Effect of the Physalis peruviana and Linum usitatissimum Extracts Against Toluene-Induced Oxidative Damages in Kidney and Liver Tissues of Rats - Gökçe, Zehra; Yılmaz, Ökkeş; Zengin, Hatayi (Nazım ŞEKEROĞLU, 2021)
. Toluen, causes a great environmental problem because it is widely used in the industry. This study was intended to examine the effect of goldenberry, Physalis peruviana (PP) and flaxseed, Linum usitatissimum (LU) extracts on the malondialdehyde (MDA), reduced glutathione (GSH) fatty acid and lipophilic vitamin content in the kidney and liver tissue of Sprague Dawley male rats which were oxidative stressed by toluene. PP and LU were extracted and subjected to vitamin and flavonoid analyses. The rats were divided into four groups as control (C), toluene (T), toluene + P. peruviana (T + PP), toluene + L. usitatissimum (T + LU). T was injected intraperitoneally at a concentration of 0.3 mL/kg. In addition, PP and LU were also injected intraperitoneally at a concentration of 0.5 mL/kg. The treatment was maintained for two months. The rats were decapitated and tissues were removed. Tissue samples were homogenized using buffer solutions. MDA, GSH, lipophilic vitamin, cholesterol and fatty acid content was determined. MDA and GSH concentration were significantly high and low in all toluene-treated groups, respectively (p<0.001). GSH level increased and the MDA concentration decreased in PP and LU treated groups (p<0.01). The palmitic (C16:0), stearic (C18:0), oleic (C18:n-9), docosahexaenoic (C22:6n-3) and arachidonic (C20:4n-6) acid concentrations were mainly higher in the kidney and liver tissues collected from the PP and LU treated groups than those collected from the control group. The K1, delta-tocopherol and alfa–tocopherol acetate vitamin concentrations were higher in PP and LU treated groups than those at group treated with the toxin group. The measured concentrations were similar to those measured in the control group. PP and LU decreased the cholesterol concentration in the kidney and liver tissues (p<0.05 and 0.01, respectively). Our results indicate that antioxidant defense systems of toluene groups have decreased. PP and LU possessed a protective feature against the oxidative stress caused by toluen.
Keywords: Structural Biology; Yapısal Biyoloji